2017
DOI: 10.1016/j.neuroscience.2015.08.044
|View full text |Cite
|
Sign up to set email alerts
|

The Val66Met brain-derived neurotrophic factor gene variant interacts with early pain exposure to predict cortisol dysregulation in 7-year-old children born very preterm: Implications for cognition

Abstract: Early stress in the form of repetitive neonatal pain, in infants born very preterm, is associated with long-term dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and with poorer cognitive performance. Brain-derived neurotrophic factor (BDNF) which is important in synaptic plasticity and cognitive functions is reduced by stress. Therefore the BDNF Val66Met variant, which affects secretion of BDNF, may interact with early exposure to pain-related stress in children born very preterm, to differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 96 publications
0
32
1
Order By: Relevance
“…Discriminant analysis by standard and forward stepwise selection method included 13 proteins, of which changes in serum concentrations in women at risk for preterm delivery have been proved in many studies [ 2 , 26 , 29 , 30 ]. We used Statistica 8.0 PL (StatSoft, Poland) with StatSoft Statistica neural networks package.…”
Section: Methodsmentioning
confidence: 99%
“…Discriminant analysis by standard and forward stepwise selection method included 13 proteins, of which changes in serum concentrations in women at risk for preterm delivery have been proved in many studies [ 2 , 26 , 29 , 30 ]. We used Statistica 8.0 PL (StatSoft, Poland) with StatSoft Statistica neural networks package.…”
Section: Methodsmentioning
confidence: 99%
“…Preterm infants are considered to suffer pain stress in early life. It has been reported that preterm boys, but not girls, with the BDNF Val66Met variant, which reduces BDNF secretion, are vulnerable to this kind of stress and show altered cognitive performance [163]. There are several explanations for these stress-related sex differences: (I) Stress can modify BDNF expression in specific brain areas based on different genders.…”
Section: Sex Differences In Stress-associated Bdnf Alterationsmentioning
confidence: 99%
“…These findings indicate that stress can influence specific brain regions, leading to altered BDNF levels correlating with mental disorders, in a sex-dependent manner. Notably, most studies examining the male-specific effect in mice and humans were carried on heterozygous individuals [162][163][164][165], which means the abnormal expression of BDNF is not confined to particular brain regions. The mechanisms underlying this sex-specific effect on BDNF may be associated with various elements, including brain regions, age, types of stressors, and species, all of which should be further clarified precisely.…”
Section: Sex Differences In Stress-associated Bdnf Alterationsmentioning
confidence: 99%
“…We identified two primary findings: (i) increased stress exposure in the NICU is associated with risk for poorer neurobehavioral outcomes and (ii) having at least one copy of the FKBP5 minor allele is also associated with the risk for poorer neurobehavioral outcomes in preterm infants. This study contributes to a growing body of literature elucidating fundamental genetic susceptibility for vulnerable infants to environmental exposures (Blair, Pickler, & Anderson, ; Chau, Cepeda, Devlin, Weinberg, & Grunau, ; Chau et al, ; Paquette et al, ). Furthermore, a significant gene x environment interaction was identified between FKBP5 genotype and stress on neurodevelopmental outcomes.…”
Section: Discussionmentioning
confidence: 84%
“…The unique novel contribution of the present study is the evidence that the polymorphism of a gene related to hormonal stress response FKBP5 contributes to effects of early procedural repetitive stress on neurodevelopment of very preterm infants. Other gene candidates have been identified as relevant for long‐term effects of invasive procedures on outcomes, for example, COMT which is related to expression of the neurotransmitter dopamine and to pain response (Chau et al, ), serotonin transporter polymorphism related to long‐term effects of stress in the presence of early trauma (Chau et al, ), and brain‐derived neurotropic factor (Chau et al, ). It is very important that future studies have large sample sizes that are needed to address multiple genetic polymorphisms and their interactions.…”
Section: Discussionmentioning
confidence: 99%